Digitalisasi Pembelajaran PAI dalam Menanggulangi Judi Online - Ansori, Yazid Al (CV. ULIL ALBAB CORP, 2024)
In the learning process, challenges are often encountered, whether in traditional or digital learning systems. In digital learning, one of the frequent challenges teachers face is negative content, such as online gambling. This poses a particular challenge for Islamic Education (PAI) teachers because they are responsible for instilling Islamic values in students. Therefore, it is essential for teachers to innovate in teaching methods to address the issue of students engaging in online gambling. The purpose of this study is to explore how online gambling among students can be mitigated through the digitalization of Islamic Education (PAI) learning. In collecting data, the researchers used observation and interviews. The results of this study at SMP Hang Tuah 4 Surabaya show that efforts to combat online gambling include innovations in PAI learning by developing online materials and utilizing digital platforms such as Canva, Instagram, and other media. Additionally, the role of PAI teachers as facilitators is maximized to ensure that Islamic values are well-instilled in students, and teachers also closely monitor students when they use their phones at school.